New KDIGO guidelines on acute kidney injury : Practical recommendations - Zarbock, A.; John, Stefan; Joerres, A.; Kindgen-Milles, D. (Anaesthesist, 2014)
The incidence of acute kidney injury (AKI) in critically ill patients is very high and is associated with an increased morbidity and mortality. In 2012 the Kidney Disease: Improving Global Outcome (KDIGO) guidelines were published in which evidence-based practical recommendations are given for the evaluation and management of patients with AKI. The first section of the KDIGO guidelines deals with the unification of earlier consensus definitions and staging criteria for AKI. The subsequent sections of the guidelines cover the prevention and treatment of AKI as well as the management of renal replacement therapy (RRT) in patients with AKI. In each section the existing evidence is discussed and a specific treatment recommendation is given. The guidelines appreciates that there is insufficient evidence for many of the recommendations. As a specific pharmacological therapy is missing, an early diagnosis, aggressive hemodynamic optimization, tight volume control, and avoidance of nephrotoxic drugs are the only interventions to prevent AKI. If renal replacement therapy is required different modalities are available to provide an effective therapy with a low rate of adverse effects.
EVALuna2:3710